The sociocultural dimension of the Software Process Improvement Manifesto: Pilot validation by experts. Issue 11 (29th July 2020) - Georgiadou, Elli; Siakas, Kerstin; Berki, Eleni; Estdale, John; Rahanu, Harjinder; Ross, Margaret
Abstract: The Software Process Improvement (SPI) Manifesto is based on three basic values: people, business focus and organisational change underpinning the philosophy of SPI. In turn, these values bring up to date certain SPI principles serving as a foundation for action in software development. The authors of this paper carried out a pilot expert validation of the sociocultural dimension of the sociocultural, technical, economic, environmental, political, legal, ethical and demographic analysis of the SPI Manifesto. Further, the authors report on the rationale and results of the pilot validation of both the survey instrument and the qualitative responses generated by the field experts, targeting to enlighten and reinforce the importance of the sociocultural dimension of the SPI Manifesto in research and development. The related literature review findings and the pilot research study strengthen this target. The pilot study with experts in particular provided stronger indications that the sociocultural dimension is considered of high importance by between 62% and 88% of the respondents, who were IT and computing professionals and software practitioners from academia and industry.